2016
DOI: 10.1039/c6ay02378a
|View full text |Cite
|
Sign up to set email alerts
|

Functional gold nanoparticles coupled with laser desorption ionization mass spectrometry for bioanalysis

Abstract: Monitoring of surface ligand and gold cluster ions produced by pulsed-laser-induced desorption/ionization of gold nanoparticles enables the transduction and amplification of mass signals for biosensing and bioimaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…To overcome the ion suppression of the targeted analytes or to analyze low abundant species, monitoring the signals produced by the desorption/ionization of the surface ligands and/or nanosubstrate cluster ions is usually more convenient. This indirect targeted approach provides higher sensitivity relative to the direct approach consisting in analyzing the signal belonging to the analytes (Unnikrishnan et al, 2016). In the "mass-tag" approach, the nanosubstrates are functionalized to bind specifically with a molecule of interest (e.g., proteins, lipids, membrane receptor,…).…”
Section: Mass-tag Reportersmentioning
confidence: 99%
“…To overcome the ion suppression of the targeted analytes or to analyze low abundant species, monitoring the signals produced by the desorption/ionization of the surface ligands and/or nanosubstrate cluster ions is usually more convenient. This indirect targeted approach provides higher sensitivity relative to the direct approach consisting in analyzing the signal belonging to the analytes (Unnikrishnan et al, 2016). In the "mass-tag" approach, the nanosubstrates are functionalized to bind specifically with a molecule of interest (e.g., proteins, lipids, membrane receptor,…).…”
Section: Mass-tag Reportersmentioning
confidence: 99%
“…and chemical (surface modification, binding energy to analytes, etc.) properties of the nanomaterials 18–23 . Gold nanoparticles (AuNP) exhibit excellent electrical conductivities, thermal and chemical stabilities and strong light absorption due to plasmonic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-assisted laser desorption/ionisation mass spectrometry (SALDI-MS) is probably the most sensitive method of detecting residual CTAB on AuNRs, since quaternary ammonium ions have a strong capacity to be desorbed and ionised in LDI-MS. 24,25 The ionisation principle of SALDI is similar to that of matrix-assisted laser desorption/ionisation mass spectrometry (MALDI-MS), [26][27][28] with the UV-absorbing organic matrix commonly used in MALDI replaced by UV-absorbing nanomaterials such as gold nanoparticles. 28 The organic matrix-free ionisation technique of SALDI-MS can avoid interference caused by organic matrix molecules in the low-mass region (below 500 Da).…”
Section: 2425mentioning
confidence: 99%
“…In particular, SALDI-MS allows highly sensitive detection of analytes adsorbed on the surface of gold nanoparticles via energy transfer from gold to the analyte. [26][27][28] For instance, Liz-Marzán and co-workers demonstrated the presence of CTAB on PEG-AuNRs by SALDI-MS. 24 Schulz and coworkers reported that although CTAB could not be identied in puried samples of PEG-AuNRs by nuclear magnetic resonance and X-ray photoelectron spectroscopy (XPS), the presence of residual CTA ions could be conrmed by SALDI-MS. 25 Thus, the development of an effective strategy for removing surfacebound CTA cations from PEG-AuNRs is highly challenging.…”
Section: 2425mentioning
confidence: 99%
See 1 more Smart Citation